Vanet performance evaluatıon ın terms of nodes dıstrıbutıon, mobılıty models, and routıng protocols - Albo Ismael, Waleed Khalid Fathi; Ucan, Osman (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Nowadays, Vehicle Ad Hoc Networks (VANETs) have become a new trend and one of the most attractive areas of research. It has a wide range of applications such as smart cities and the Internet of Things (IoT). The main issue of the VANET networks is the limitation in network resources such as power, and memory. Moreover, since VANET nodes are dynamic and move over time, the connectivity of the networks is also considered an important issue. This paper designs experiments that reflect a variety of scenarios in VANET networks. Many issues and factors in VANET networks have also been investigated in this paper. There are many factors that affect the whole performance of VANET networks (i.e., mobility models, routing protocols, and things distribution) in terms of network resources. Therefore, this paper aims at testing different mobility models such as the Human Mobility model, Cauchy Flight Mobility model, and Correlated Directions Mobility model, and investigate their impact on the consumption of network resources under a particular routing protocol such as Spray and Wait routing protocol, Probabilistic Flooding routing protocol, and Epidemic routing protocol. In addition, testing different distributions such as Uniform distribution, Gaussian (Normal) distribution, and Power-Law distribution). The resources we plan to investigate are energy sources and the amount of data exchanged. In the designed experiments, each simulation includes a combination of a mobility model, nodes distribution, and a routing protocol. The findings showed that each mobility model, routing protocol, or distribution is effective in a particular application. As a result, it was found that determining the application of the VANET network is a crucial step before performing a simulation or designing a network.